Pengaruh Health Promotion Model “Nola J. Pender” Berbasis Komunitas Terhadap Pencegahan Merokok pada Remaja Putra di Kecamatan Jaya Baru Kota Banda Aceh - Mardhiah Mardhiah; Fitriani Agustina; Teuku Tahlil; Ambia Nurdin; Anda Syahputra (Lembaga Teewan Journal Solutions, 2026)
Background: Smoking remains a persistent behavioral phenomenon among adolescents, frequently driven by peer pressure, social perceptions of masculinity, a lack of community-enforced norms, and local religious views. Objective: This study aimed to evaluate the effect of a community-based health promotion intervention using Nola J. Pender’s Health Promotion Model (HPM) on smoking prevention among adolescents in Banda Aceh. Methods: A quasi-experimental study with a one-group pre-posttest design was conducted on 30 adolescents selected via probability sampling. Smoking status, knowledge, attitude, and perception variables were measured using an adapted questionnaire from the Global Youth Tobacco Survey (GYTS) version 1.2. The self-esteem variable was assessed using the Rosenberg Self-Esteem Scale (RSES). Bivariate analyses were performed using the Wilcoxon Signed-Ranks Test and Paired Sample T-Test. Results: The analysis demonstrated a significant decrease in smoking status post-intervention (Z= -4.497; p = 0.001). Significant increases were also observed in knowledge, attitudes, and perceptions (t= 10.205; p= 0.001), as well as in adolescent self-esteem (t= 5.950; p= 0.001). Conclusion: Community-based health promotion utilizing Nola J. Pender’s HPM framework is highly effective in reducing smoking status and enhancing knowledge, attitudes, perceptions, and self-esteem among adolescents. This intervention underscores the importance of integrating HPM-based models into community-level adolescent health programs.